Toward a Radically Simple Multi‐Modal Nasal Spray for Preventing Respiratory Infections - Joseph, John; Baby, Helna Mary; Quintero, Joselyn Rojas; Kenney, Devin; Mebratu, Yohannes A; Bhatia, Eshant; Shah, Purna; Swain, Kabir; Lee, Dongtak; Kaur, Shahdeep; Li, Xiang‐Ling; Mwangi, John; et al. (Advanced materials (Weinheim), 2024)
Nasal sprays for pre‐exposure prophylaxis against respiratory infections show limited protection (20–70%), largely due to their single mechanism of action—either neutralizing pathogens or blocking their entry at the nasal lining, and a failure to maximize the capture of respiratory droplets, allowing them to potentially rebound and reach deeper airways. This report introduces the Pathogen Capture and Neutralizing Spray (PCANS), which utilizes a multi‐modal approach to enhance efficacy. PCANS coats the nasal cavity, capturing large respiratory droplets from the air, and serving as a physical barrier against a broad spectrum of viruses and bacteria, while rapidly neutralizing them with over 99.99% effectiveness. The formulation consists of excipients identified from the FDA's Inactive Ingredient Database and Generally Recognized as Safe list to maximize efficacy for each step in the multi‐modal approach. PCANS demonstrates nasal retention for up to 8 hours in mice. In a severe Influenza A mouse model, a single pre‐exposure dose of PCANS leads to a >99.99% reduction in lung viral titer and ensures 100% survival, compared to 0% in the control group. PCANS suppresses pathological manifestations and offers protection for at least 4 hours. This data suggest PCANS as a promising daily‐use prophylactic against respiratory infections. A pathogen capture and neutralizing spray (PCANS) is reported to prevent respiratory infections through a multi‐modal approach. PCANS coats the nasal cavity, capturing large respiratory droplets and serving as a physical barrier against viruses and bacteria, while neutralizing them with over 99.99% effectiveness. In mice, PCANS shows nasal retention for ≈8 hours and offers pre‐exposure protection against lethal viral infections.